Role of Social Media in Cyber Security: Addressing the Challenges of Cyber Security in the Age of Social Media (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cyber crime keeps on wandering down various ways with each New Year that passes thus does the security of the data. The most recent and problematic innovations, alongside the new cyber apparatuses and dangers that become known every day, are testing associations with how they secure their framework, yet how they require new stages and insight to do as such. There is no ideal answer for cyber crimes except for we should attempt our level best to limit them to have a free from any danger future in cyber space. cyber-security is both with regards to the insecurity made by and through this new space and about the practices or systems to make it (continuously) secure. Effort to check the cyberspace should give an authoritative need else the data technology won't be reasonably utilized by customers. The terrorist of things to come will win the conflicts without releasing a shot just by pounding the country's vital base assuming advances are not taken to deal with the inescapability of the development in such a cyber-attack.